Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Bridging the edtech evidence gap: A realist evaluation framework refined for complex technology initiatives - King, Melanie; Rothberg, Steve; Dawson, Ray; Batmaz, F. (Journal of Systems and Information Technology, 2016)
Purpose – There are five factors acting as a barrier to the effective evaluation of educational technology (edtech), which are as follows: premature timing, inappropriate techniques, rapid change, complexity of context and inconsistent terminology. The purpose of this paper is to identify new evaluation approaches that will address these and reflect on the evaluation imperative for complex technology initiatives. Approach – An initial investigation of traditional evaluative approaches used within the technology domain was broadened to investigate the evaluation practices within social and public policy domains. Realist evaluation, a branch of theory-based evaluation, was identified and reviewed in detail. The realist approach was then refined, proposing two additional necessary steps to support mapping the technical complexity of initiatives. Findings – A refined illustrative example of a realist evaluation framework is presented, including two novel architectural edtech domain reference models to support mapping. Practical implications – Recommendations include building individual evaluator capacity; adopting the realist framework; the use of architectural edtech domain reference models; phased evaluation to first build theories in technology “context” and then iteratively during complex implementation chains; and community contribution to a shared map of technical and organisational complexity. Originality – This paper makes a novel contribution by arguing the imperative for a theory-based realist approach to help redefine evaluative thinking within the IT and complex system domain. It becomes an innovative proposal with the addition of two domain reference models that tailor the approach for edtech. Its widespread adoption will help build a shared evidence base that synthesizes and surfaces “what works, for whom, in which contexts and why”, benefiting educators, IT managers, funders, policymakers and future learners.